(untitled) (JURNAL ULET (Utility, Earning and Tax), 2023)
This research was conducted to determine the level of solvency of PT Mustika Ratu Tbk. The method used is descriptive method. Data collection techniques using documentation techniques, in this case researchers collect data in the form of company documents, literature studies, in this case researchers collect library sources related to research. The results of this study indicate that the solvency level of PT Mustika Ratu is classified as good where the solvency ratio which can be seen in the Debt to Equity Ratio is below 50% and the capital structure that provides a balance between risk and return so that the return on capital can be maximized which is characterized by more funding for company activities. financed by the company’s capital rather than debt.